Checklist for a complete chronic urticaria medical history : an easy tool (2017)
ABSTARCT: Existing guidelines do not offer a quick, efficient alternative to the patient's recollection of relevant clinical features during anamnesis and physical examination for chronic urticaria (CU). This study aimed to identify specific items reflecting the main characteristics of CU that should be included in a comprehensive medical history for patients with CU. We also aimed to clarify possible eliciting factors for CU to support accurate diagnosis of the disease. METHODS: A panel of postgraduate dermatologists conducted a literature search for relevant studies on CU using Medline, the Cochrane database, and PubMed. RESULTS: We identified82 articles from which we drew a collection of items to inform development of an easy-to-use checklist and collection of items that should be included in a correct medical history. The final version of the checklist included42 items across two areas: essential clues for anamnesis and diagnosis of CU; and typical symptoms/parameters or characteristics according to subtype, etiology, and laboratory findings. Items included time of disease onset; duration, shape, size, color, and distribution of wheals; associated angioedema; atopy; and triggering factors. CONCLUSIONS: Our guide provides an easy-to-use tool to support clinicians to focus, orient themselves, and save time in medical consultations for CU, allowing better diagnosis and management of this disease.